The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1088/0022-3727/49/10/105204
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the anode boundary layer in atmospheric pressure arc discharges

Abstract: The anode boundary layer in atmospheric pressure arc discharges is studied numerically on the basis of the hydrodynamic (diffusion) equations for plasma components. The governing equations are formulated in a unified manner without the assumptions of thermal equilibrium, ionization equilibrium or quasi-neutrality. For comparison, a quasi-neutral model of the anode layer is also considered. The numerical computations are performed for an argon arc at typical values of the current density in anode layers (500–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…However, such uni…ed modelling is highly computationally intense in the case of arc plasmas, where the charge particle density is very high, space-charge sheaths occupy only a tiny fraction of the computation domain, and the separation of charges in the bulk plasma is very small. Up to now this approach has been applied only to one-dimensional (1D) models of near-cathode and near-anode regions which separate the electrodes from the bulk of the arc where local thermodynamic equilibrium (LTE) holds [13][14][15].…”
Section: Uni…ed Modellingmentioning
confidence: 99%
See 3 more Smart Citations
“…However, such uni…ed modelling is highly computationally intense in the case of arc plasmas, where the charge particle density is very high, space-charge sheaths occupy only a tiny fraction of the computation domain, and the separation of charges in the bulk plasma is very small. Up to now this approach has been applied only to one-dimensional (1D) models of near-cathode and near-anode regions which separate the electrodes from the bulk of the arc where local thermodynamic equilibrium (LTE) holds [13][14][15].…”
Section: Uni…ed Modellingmentioning
confidence: 99%
“…A variant of the approach employing the LTE description of the bulk plasma was considered in [41,42]. Another variant of this approach can in principle be developed on the basis of simulations [13][14][15].…”
Section: Other Possible Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Though arcs has been extensively studied earlier, most of the studies considered only specific aspects of the arc physics: cathodic region 7,8,9,10,11,12,13 , arc column 14,15 , anodic region 16,17,18,19,20,21,22,23,24 . A detailed review of works on argon arc modeling can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%